Assessment of Portunus (Portunus) trituberculatus (Miers, 1876) stock in the northern East China Sea - Wang, Yingbin; Gao, Li; Chen, Yunxia (Indian Journal of Fisheries, 2018)
Portunus (Portnus) trituberculatus (Miers, 1876) is one of the important commercial crustaceans in the northern East China Sea. Although extensive research on aquaculture of the species is being carried out, the wild stock is scientifically unassessed. In this paper, the total catch of P. trituberculatus in the northern East China Sea during 2001 and 2015 were classified into 4 carapace width (CW) groups (150 mm), for estimation of the maximum sustainable yield (MSY) and the spawner-recruitment relationships for wild stock and released stock were built, respectively. Standing biomass, spawning biomass and catch were predicted under the assumptions that fishing intensity and quantity of P. trituberculatus released were kept at the levels of those in 2015. The results showed that the MSY of P. trituberculatus is about 14.2×104 t and the corresponding fishing effort (EMSY) is about 14.8×104 tonnage (both the crab pot vessels and trawl vessels were standardised to gillnet vessels). In future, if fishing effort level and the release number equals to those in 2015, the biomass, spawning biomass and catch of P. trituberculatus would remain at 58.9×104 t, 53.1×104 t and 15.6×104 t, respectively. The present stock assessment study was conducted with limited data and further survey data in future may provide more accurate stock assessment to evolve management strategies.